Meaning Agnosticism and Pragmatism - Sami Pihlström (Religions, 2020)
This paper proposes to reconsider agnosticism by taking a step onto a meta-level, investigating agnosticism not as an epistemic stance regarding the choice between theism and atheism, but as a stance toward the question concerning the cognitive meaningfulness and/or truth-aptness of religious discourse. It is argued that this “meta-level” meaning agnosticism may actually be an attractive articulation of a certain kind of religious attitude. While pragmatists like William James have claimed that (epistemic) agnosticism practically collapses into atheism, meaning agnosticism at the meta-level can in fact be a pragmatist position focusing on our human condition and its limits. Additional issues, such as the relations between agnosticism and the theodicism vs. antitheodicism debate regarding the problem of evil and suffering, are also briefly examined.